A single summative global scale of disordered eating attitudes and behaviors: Findings from Project EAT, a 15-year longitudinal population-based study. (December 2020) - Yoon, Cynthia; Simone, Melissa; Mason, Susan; Neumark-Sztainer, Dianne
Abstract: Objective: The Project EAT Disordered Eating Attitudes and Behaviors (DEAB) scale was created from disordered eating attitudes and behaviors that tend to interrelate. To examine the appropriateness of the scale, we assessed the fit (i.e., how well a single latent factor fits a set of interrelated disordered eating attitudes and behaviors) and the convergent validity over time. Method: Five interrelated disordered eating attitudes and behaviors were assessed in a longitudinal cohort (Project EAT, age 11 to 18 in 1998–1999, N  = 1492). Confirmatory factor analysis examined the appropriateness of the DEAB scale. To examine whether individual variables function differently in relation to the latent construct across time, two models were compared: one requiring indicator-level factor loadings to remain equivalent across three time points (baseline [EAT-I], five-year follow-up [EAT-II], and 15-year follow-up [EAT-IV]), and the second allowing the factor loadings to vary over time. To examine the convergent validity, Pearson correlation with body satisfaction, self-esteem, depressive symptoms, and BMI was compared across time. Results: The fit indices for a single factor structure supported the use of the DEAB scale over time (standardized loadings: 0.60–0.87, 0.67–0.89, 0.59–0.77 at EAT-I, II, and IV respectively). As hypothesized, compared to fewer number of disordered eating attitudes and behaviors, greater number of attitudes and behaviors was associated with lower body satisfaction and self-esteem, and greater depressive symptoms and BMI ( p  < .01). Discussion: The Project EAT DEAB scale can be used as a proxy to measure the severity of disordered eating attitudes and behaviors over time in population-based studies. Highlights: The five disordered eating attitudes and behaviors assessed in this study exist on a single dimension. The unidimensional disordered eating attitudes and behaviors (DEAB) scale is stable and psychometrically valid. The DEAB scale may indicate the severity of disordered eating attitudes and behaviors among adolescents.